Erythropoietin Triggers a Signaling Pathway in Endothelial Cells and Increases the Thrombogenicity of their Extracellular Matrices In Vitro - Fusté, Berta; Serradell, Mireia; Escolar, Ginés; Cases, Aleix; Mazzara, Roberto; Castillo, Ricardo; Ordinas, Antonio; Díaz-Ricart, Maribel (Thrombosis and Haemostasis, 2002)
We demonstrate that exposure of cultured human endothelial cells to rHuEPO resulted in a dose-dependent increase in the tyrosine kinase activity, with phosphorylation of JAK-2 followed by rapid phosphorylation of STAT-5. Simultaneously, rHuEPO induced long-lasting phosphorylation of MAPK p42/44. Activation of this signaling pathways was directly associated with an increase in the thrombogenic properties of the extracellular matrix generated by these cells, when they were exposed to flowing blood. The enhancement in the reactivity of the resulting extracellular matrix towards platelets was associated with a higher expression of tissue factor. All these effects were blocked by an antibody to the EPO receptor and by specific inhibitors of tyrosine phosphorylation. The observed action of rHuEPO on endothelial cells seemed to be specifically triggered by the subsequent events that follow receptor binding, and occurred even at pharmacological concentrations of the cytokine. Our results indicate that rHuEPO has a direct action on the endothelium, increasing the reactivity of the underlying extracellular matrix towards platelets, effect that may be attributed to an increase in the expression of TF.
Keywords: Erythropoietin; endothelium; tyrosine phosphorylation; thrombosis; tissue factor